Applying the marketing mix to the analysis of the barley market in the European context - Elena Cofas (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
Barley is a plant cultivated as an herbage plant, which has therapeutic qualities, being relatively well represented in all the Romanian culture areas where it finds appropriate culture conditions. The fact that there are autumn and spring forms may be the reason why this species occupies an important place in the farmer's crop decision, especially when the market offers a price and a guarantee of purchase since the establishment of crops. Occupying almost 5% of the arable land (about 440.4 thousand ha of barley versus 9.3 million hectares of arable land), barley is associated with wheat in cereal-based farms because it does not have any particular fundamental technological requirements. Because of the attractive price, barley can successfully replace wheat. The specific development of marketing activity in agricultural holdings requires changing the way the cereal market is analyzed, from the traditional approach - by analyzing market demand and supply - to a modern approach - by analyzing the marketing mix. This research aimed at analyzing the barley culture market through the mix of marketing, which led to the analysis of all the characteristic elements (product, price, placement, promotion) - practically an analysis both in terms of cultivated surfaces, production and price of culture barley, and marketing tools whose implementation determines the evolution of products and market prices. The results of the research of the marketing mix elements on the barley market and its products have shown positive aspects of the development of this market, as the economic importance of barley crops is lower compared to wheat, corn, rice or rye.
Keywords: O12; P50; Q18; Q57; 330; barley; analyze; market; price; marketing mix